Congenital hyperinsulinism disorders: Genetic and clinical characteristics. Issue 4 (14th August 2019) - Rosenfeld, Elizabeth; Ganguly, Arupa; De Leon, Diva D.
Abstract: Congenital hyperinsulinism (HI) is the most frequent cause of persistent hypoglycemia in infants and children. Delays in diagnosis and initiation of appropriate treatment contribute to a high risk of neurocognitive impairment. HI represents a heterogeneous group of disorders characterized by dysregulated insulin secretion by the pancreatic beta cells, which in utero, may result in somatic overgrowth. There are at least nine known monogenic forms of HI as well as several syndromic forms. Molecular diagnosis allows for prediction of responsiveness to medical treatment and likelihood of surgically‐curable focal hyperinsulinism. Timely genetic mutation analysis has thus become standard of care. However, despite significant advances in our understanding of the molecular basis of this disorder, the number of patients without an identified genetic diagnosis remains high, suggesting that there are likely additional genetic loci that have yet to be discovered.